2020
DOI: 10.1096/fj.201901777r
|View full text |Cite
|
Sign up to set email alerts
|

S100A6 is a positive regulator of PPP5C‐FKBP51‐dependent regulation of endothelial calcium signaling

Abstract: ISOC is a cation current permeating the ISOC channel. In pulmonary endothelial cells, ISOC activation leads to formation of inter‐endothelial cell gaps and barrier disruption. The immunophilin FK506‐binding protein 51 (FKBP51), in conjunction with the serine/threonine protein phosphatase 5C (PPP5C), inhibits ISOC. Free PPP5C assumes an autoinhibitory state, which has low “basal” catalytic activity. Several S100 protein family members bind PPP5C increasing PPP5C catalytic activity in vitro. One of these family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Moreover, we have found interesting candidates in the HeLa proteome profiling that could explain or be related to the mentioned cellular disturbances (Figure 3C). S100A6, underexpressed, is a positive regulator of proliferation, migration and angiogenesis [60]- [62], and also a regulator of endothelial calcium signalling [63]. PKM, which was over-expressed in HeLa cells, is associated with apoptosis resistance [64].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have found interesting candidates in the HeLa proteome profiling that could explain or be related to the mentioned cellular disturbances (Figure 3C). S100A6, underexpressed, is a positive regulator of proliferation, migration and angiogenesis [60]- [62], and also a regulator of endothelial calcium signalling [63]. PKM, which was over-expressed in HeLa cells, is associated with apoptosis resistance [64].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc can also bind tau directly to contribute to tau toxicity independent of tau hyperphosphorylation [134, 135]. S100A6 can also enhance the phosphatase activity of PPP5C towards p-tau [136]. Together, this data shows the novel astrocyte-oligodendrocyte hybrid cells overexpress neurotrophic factors in conjunction with suppression of EIF2-mediate stress response, suggesting a potential neuroprotective function or homeostatic role.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc can also bind tau directly to contribute to tau toxicity independent of tau hyperphosphorylation 57, 58 . A recent report has revealed that S100A6 can also enhance the phosphatase activity of PPP5C towards p-tau 59 . This data further strengthens the idea that the hybrid subpopulation is associated with potential neuroprotective functions.…”
Section: Discussionmentioning
confidence: 99%